Investigating Individuals’ Intention to be Involved in Knowledge Management Process - Mohamed Razi, Mohamed Jalaldeen; Nor Shahriza , Abdul Karim (Science Publications, 2011)
Implementation of Knowledge Management (KM) process in organizations is considered as essential to be competitive in the present competitive world. Though the modern KM practices highly depend on technology, individuals (‘organizational members’) intention to be involved in KM process plays a major role in the success. Hence, the evaluation of individuals’ intention is deemed as significant before the actual implementation of KM process in organizations. Nevertheless, inadequate information is presented in this regard; as a result, a wide research gap prevails in the literature. In this context, the present study focuses on developing a research frame work that can be used to measure the individual intention to be involved in KM process. Approach: Subsequent to a critical analysis of the research gaps, a basic research model has been developed based on knowledge creation theory, KM enablers, and individual acceptance model. Measurers and questionnaire items were identified for each variable from relevant literature. Consequently, the reliability of the instrument was tested among academic staff of a Malaysian university. Results: The Cronbach’s alpha for each variable is more than 0.800 that exhibits the reliability of the instruments. Conclusion: The presented research framework might be a doorstep for future study in this area of KM. Moreover, practitioners may use the proposed framework to measure the intention of individuals to be involved in KM process before actually embarking to it. However, the framework and the model should be tested in different socio cultural and organizational climate to make it robust.